Identification of Seasonal and Annual Groundwater Level Trends in Temperate Climatic Conditions - Minea, Ionuț; Boicu, Daniel; Amihăiesei, Vlad; Iosub, Marina (Frontiers in Environmental Science, 2022)
The management of groundwater resources must take into account their variation trends. In this sense, 3 statistical methods were used to identify seasonal and annual groundwater level trends: Mann-Kendall test (MK), Innovative Analysis Method (ITA) and Spearman’s Rho test (SR). Each method was applied for 5 time series (one annual and 4 seasonal) from 148 hydrological wells from Eastern Romania. The wells were classified in 8 cluster groups based on water depth, using the cluster analysis, covering the full range of depths from under 1.4 to over 15.5 meters. Coupling statistical methods (MK and SR test) with one based on graphical analysis (ITA method) offers the possibility of obtaining statistically significant results (between 53% and 69% for spring season, 68% and 96% for autumn season and 68% and 81% from annual values). The decreasing trend of water depth is more obvious for summer and autumn season, for 72-74% from analyzed wells (based on SR and ITA method) and 68% for annual series (based on MK test). The spatial distribution of seasonal and annual trends highlights that in the northern and central parts of the region, the groundwater depth suffers depletion induced by the effects of prolonged meteorological and hydrological drought manifested in this area in the last decades.